Design of the SVC Control Strategy for Fast Load and its Application - 刘华东; 张定华; 谭胜武 (Kongzhi Yu Xinxi Jishu)
For the compensation requirements of fast load, it proposes a principle of load compensation based on the instantaneous value. Using instantaneous reactive power theory, the detections on both reactive current and active current of instantaneous positive/negative sequence are realized, and the calculation of ideal compensator ’s compensation admittance is also obtained. Furthermore, in order to achieve the rapid response and good steady-state accuracy, a SVC control strategy of overall open-loop & part closed-loop is proposed, and the trigger mode of thyristor valves is also improved. The results of test and field running show that the SVC control strategy can meet the requirements of the fast load compensation, improves the flicker suppression and has good guidance for engineering practice.